Evaluation of the Management of the Integrated Antenatal Care Program by Midwives for Pregnant Women at the Kenali Besar Health Center Jambi City in 2022 - Afifah Farras Hasalia; Dwi Noerjoedianto; Hubaybah Hubaybah (Rifa'Institute, 2022)
The Integrated Antenatal Care (ANC) program is the standard of success in health services, because Antenatal Care is a comprehensive service for pregnant women in early detection of pregnancy complications that may occur to prepare for positive pregnancy and childbirth, so as to reduce maternal mortality. However, the maternal mortality rate in Jambi City still occurs every year, therefore one of the objectives of the Integrated Antenatal Service Program is to reduce the Maternal Mortality Rate (MMR). This study uses a qualitative research method with a case study approach with a total of 10 informants. Data were collected through in-depth interviews, observation, and document review. The results of this study on the input aspect are not good, because Health HR is still lacking in midwives and the facilities and infrastructure that must be owned. In the aspect of the process, it was found that it was not good, because HR planning was not carried out, the implementation process in providing services according to the 10 T standard was also not maximized and recording and reporting often resulted in delays in reporting and recording.